Global ethics and environment - Low, Nicholas (Routledge, 1999)
As global capitalism expands and reaches ever-further corners of the world, practical problems continue to escalate and repercussions become increasingly serious and irreversible. These practical problems carry with them equally important and ethical issues. Global Ethics and Environment explores these ethical issues from a range of perspectives and using a wide range of case studies. Chapters focus on: the impact of development in new industrial regions; the ethical relationship between human and non-human nature; the application of ethics in different cultural and institutional contexts; environmental injustice in the location of hazardous materials and processes; the ethics of the impact of a single event (Chernobyl) on the global community; the ethics of transitional institutions. This collection will both stimulate debate and provide an excellent resource for wide-ranging case study material and solid academic context.